TWO DECADES OF DISCORD AND DIALOGUE: A COMPREHENSIVE ANALYSIS OF INDIA-CHINA BORDER NEGOTIATIONS (2000–2020) - Ganiger, Santosh Mallappa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the twenty-first century, the India-China border issue has veered between hostility and diplomacy due to unresolved territorial claims that date back to the 1962 war. With an emphasis on the interplay of conflict and communication in handling their Himalayan border dispute, this study offers a thorough examination of the diplomatic and military exchanges between China and India between 2000 and 2020. The study looks at the structural and immediate causes of tensions as well as institutional de-escalation mechanisms using a mixed-methods approach that combines historical analysis of bilateral agreements, crisis events (such as the 2013 Depsang standoff, 2017 Doklam crisis, and 2020 Galwan Valley clash), and official statements. The study finds a cyclical pattern: recurrent border standoffs frequently followed times of economic cooperation and multilateral participation (e.g., BRICS, SCO), highlighting the duality in bilateral relations. Territorial disputes continued in spite of frameworks such as the Special Representatives discussion and the 2003 Declaration on Principles, which were made worse by the militarization of infrastructure (such as China's Belt and Road Initiative and India's border road projects). The worst conflict in forty-five years, the 2020 Galwan Valley fight, was a low point that exposed the weakness of confidence-building measures (CBMs) and the emergence of nationalist rhetoric in both countries. While both states stressed strategic patience to prevent full-scale conflict, the report contends that shifting alliances and opposing geopolitical aspirations (such as India's developing U.S. relations) led to a deepening of mutual mistrust. Diplomatic flexibility was further limited by media-driven nationalism and domestic political narratives. The study concludes that a lasting resolution is still difficult unless fundamental territorial claims are addressed, military deployments are made more transparent, and economic links are shielded from security crises by placing these dynamics inside larger theoretical discussions on diplomacy and deterrence. In addition to providing policy insights for maintaining Indo-Pacific stability, this work advances the field of study on asymmetric wars.